ChemInform Abstract: A Highly Enantioselective Thiolation of Sulfonyl Indoles to Access 3‐sec‐Sulfur‐Substituted Indoles in Water. Issue 17 (April 2016) - Chen, Ping; Lu, Sheng‐mei; Guo, Wengang; Liu, Yan; Li, Can
Abstract: Vinylogous imine intermediates generated in situ from sulfonylindoles undergo asymmetric 1, 4‐addition with trityl mercaptan (I) to form the title compounds with good to excellent enantioselectivities.